2012
DOI: 10.1002/anie.201206489
|View full text |Cite
|
Sign up to set email alerts
|

An RNA–Deaminase Conjugate Selectively Repairs Point Mutations

Abstract: Checking for mistakes: By conjugating a catalytic domain with a guide RNA, deamination activity can be harnessed to repair a specific codon on mRNA. This method can be used for the highly selective repair of point mutations in mRNA by site-selective editing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 22 publications
0
106
0
3
Order By: Relevance
“…Full A-to-I conversion at the targeted site (A200) was achieved (Figure 1B, (a)). However, in contrast to our engineered SNAP-ADAR deaminase, (34,42) wild-type ADAR2 was dramatically more reactive and gave massive off-target editing, with full conversion at A381 (Figure 1B, (a)), 50–70% yield at A295, A380, A476 and minor editing at various sites (Supplementary Figure S2). This off-site editing was typically guideRNA-independent.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Full A-to-I conversion at the targeted site (A200) was achieved (Figure 1B, (a)). However, in contrast to our engineered SNAP-ADAR deaminase, (34,42) wild-type ADAR2 was dramatically more reactive and gave massive off-target editing, with full conversion at A381 (Figure 1B, (a)), 50–70% yield at A295, A380, A476 and minor editing at various sites (Supplementary Figure S2). This off-site editing was typically guideRNA-independent.…”
Section: Resultsmentioning
confidence: 66%
“…A reporter mRNA (cyan fluorescent protein) that contains a single G-to-A point mutation generating a nonsense stop signal (Trp 66 →amber) served as substrate (Figure 1), as described before (34,42). Wild-type human ADAR2 was expressed and purified from yeast (YVH10), as described before (42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By introducing RNA oligonucleotides complementary to a premature termination codon, Woolf et al induced endogenous ADAR to nonspecifically edit the region, including the premature termination codon, both in vitro and in Xenopus embryos (33). A recent study has reported a more directed approach, similar to our own (34). In it the authors coupled the catalytic domain of human ADAR1 to a guide RNA oligonucleotide using an in vitro reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Guide-RNAs not only allow mRNA target specificity but more importantly induce the formation of secondary structures necessary for achieving highly efficient and selective targeting of a single adenosine, without the risk of over-editing. Additional studies have shown efficient in vitro correction of a stop codon introduced into a fluorescent protein, and at CFTR W496X and EGFP W58X, by using a similar approach coupling the catalytic domain of ADAR1 to a guideRNA [88,89]. Although these studies improved the prospect of directed RNA editing for in vivo applications and medicine, many parameters remain without optimization, including mode of delivery.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%